Information Content of Option Implied Volatility in Europe - Ingström, Veli-Petteri (My University, 2015)
The purpose of this thesis is to research the implied volatility forecasts given by major European volatility indices during the last 15 years. Implied volatilities of the options of major stock indices give information of expected overall volatility i.e. systematic risk. VIX is a good example of the use of implied volatility in quantifying the level of systematic risk. Implied volatilities of options are often used to forecast future realised volatility. Option implied volatility is the theoretically correct way to forecast future volatility, as it represents the market´s consensus expectation of future volatility. According to the efficient market hypothesis, the forecast should include all relevant publicly available information. If implied volatility forecasts overestimated future realized volatility, it would be an indication of option market inefficiency. Overly high implied volatilities compared to future realized volatility, could also mean that the particular options are overpriced. During the financial crisis VIX reached a record high level. VIX is constructed of S&P 500 index options and measures the expected volatility over the next 30 days, which is then annualized. After the bankruptcy of Lehman Brothers, VIX went as high as 80 % expected annual volatility. At least intuitively such high levels of expected volatility would seem overestimated, and might be proof of a panic reaction by the market. The implied volatilities during the financial crisis are a relatively new topic and there have been only a handful of similar studies. This is why the subject is worth investigating. The thesis uses DAX 30, FTSE 100, EURO STOXX 50 and SMI stock indices and their corresponding volatility indices. Statistical methods consist of standard regression analysis. This thesis concludes that implied volatility contains incremental information of future stock market volatility, but is a biased and inefficient estimator. The information content of implied volatility is still very high and it subsumes all relevant information from past realized volatility.
Keywords: implied volatility; option; volatility forecasting; volatility index; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|